Translating School Physical Education and Activity Policies into Practice: A Case Study. Issue 12 (2020) - O'Hara Tompkins, Nancy; Northrup, Karen; Grant, Josh; Weikle, Mary Foltz; Long, Dustin; Bassler, John; Workman, Charlotte; Ramsey, Zachary; Jarrett, Traci; Sirk, Hannah; Cottrell, Lesley
ABSTRACT: Background: Public health experts recommend school-based policies as a population-based approach to increase youth physical activity. The purpose of this case study is to describe one, largely rural, state's efforts to translate this recommendation into practice. Details about the genesis, implementation, and evolution of two state-level policies (physical education and physical activity), as well as in-house efforts of a State Department of Education to monitor policy compliance and challenges encountered are described. Two specific years are highlighted because of policy and monitoring enhancements made during those particular time periods. Methods: Data for this article come from the West Virginia Department of Education for two time periods: 2013–2014 and 2014–2015 ( n = 369 elementary schools). Descriptive statistics for quantitative data and content analysis for qualitative data were used to document school-level compliance and provide context for implementation challenges. Results: Greater than 70% of school principals reported achievement of physical education and physical activity policy expectations for each year. Limited staff was the predominant explanation for nonfulfillment of physical education expectations, followed by lack of time and facilities. Recess and classroom-based physical activity were the primary strategies used to comply with the physical activity expectations. Physical education and physical activity policy compliance varied significantly by certain school characteristics in each school year studied. Conclusions: Further investigation is warranted on how states translate public health policy recommendations into practice, including how physical education and physical activity policies are developed and monitored at the state level and how to support states and schools with monitoring and implementation challenges.